PELATIHAN EDUECOPRENEURSHIP SEBAGAI SOLUSI PENDIDIKAN DAN PEMBERDAYAAN EKONOMI BAGI PEKERJA MIGRAN INDONESIA DI BRUNEI DARUSSALAM - Wasis Wasis; Rooselyna Ekawati; Yurizka Melia Sari; Pardamean Daulay; Sifak Indana; Titin Sunarti; Nonik Indrawatiningsih; Mukhayyarotin Niswati Rodliyatul Jauhariyah; Sari Kusuma Dewi; Findiyani Ernawati Asih; Reny Amalia Permata; Annisa Rahmita Soemarsono (Jurnal ABDI: Media Pengabdian Kepada Masyarakat, 2026)
Indonesian Migrant Workers (PMI) in Brunei Darussalam face limited access to continuing education, lack of entrepreneurial skills, and insufficient understanding of the integration between education, ecology, and business. To address this gap, the FMIPA team from Universitas Negeri Surabaya conducted an online EduEcopreneurship training in November 2025. The activity employed a participatory workshop approach and a pretest-posttest evaluation design. Results indicated a significant improvement in participants’ conceptual understanding, with average scores rising from 52.4 to 84.2 (a 31.8-point increase, or 60.7%). Moreover, 93.3% of participants successfully designed business ideas that integrated the three core pillars of EduEcopreneurship: Eco-Innovation, Eco-Opportunities, and Eco-Commitment. Participant feedback was rated “Good” (average 4.08 on a 5-point scale). These findings confirm that EduEcopreneurship serves as an effective dual empowerment model,combining non-formal education and sustainable economic development,for migrant workers.